1996
DOI: 10.4172/plastic-surgery.1000135
|View full text |Cite
|
Sign up to set email alerts
|

Congenital giant pigmented nevi: Clinical features and risk of malignancy

Abstract: Surg 1996;4(2):94-98. There is general agreement that congenital giant pigmented nevi (CGPN) are precursors to malignant melanoma; however, the magnitude of the risk of malignant transformation is the subject of wide controversy. The goal of this study was to present the authors' experience with CGPN and more specifically their experience with the risk of malignancy. To identify the general features of CGPN a detailed retrospective chart review was performed at The Hospital for Sick Children in Toronto (1979To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
0
8
0
3
Order By: Relevance
“…The risk of malignant degeneration as well as psychosocial morbidity from disfigurement merit resection of these lesions [1,2]. Melanocytic nevi can be classified as "small", "medium", "large", or "giant" based on their dimensions in centimeters or by TBSA; although, a consensus definition does not exist [7,[13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of malignant degeneration as well as psychosocial morbidity from disfigurement merit resection of these lesions [1,2]. Melanocytic nevi can be classified as "small", "medium", "large", or "giant" based on their dimensions in centimeters or by TBSA; although, a consensus definition does not exist [7,[13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria were: (1) lesions that required at least 3 excisions to remove and (2) melanocytic congenital that could have been managed with skin grafting or tissue expansion. Patient age, gender, location of the lesion, size of the nevus [% total body surface area (TBSA)] [2,6,7], number of serial excisions, histopathology, and complications were recorded. Data are presented as mean with standard deviation or range.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple reports [2][3][4][5][6][7][8][9][10][11][12] regarding the risk of malignant degeneration of this neuroectodermal malformation have been published, but information regarding large numbers of affected persons has been nonexistent. In this article, the characteristics of 1008 such persons are described.…”
mentioning
confidence: 97%
“…In addition, concerns about lack of parameters to predict as to which nevi are susceptible to malignant transformation, compounded with the fact that the diagnosis gets delayed and the course in case of a malignant change is invariably fatal are reasonable [5]. A recent review [8] has concluded that an early aggressive approach to these lesions is responsible for the low risk of malignant melanoma reported in various series. Surgical excision results in the debulking of tissue at risk for the development of malignant melanoma.…”
Section: Discussionmentioning
confidence: 99%